Non-mental health workers' attitudes and social distance towards people with mental illness in a Nigerian teaching hospital - Olatunji F. Aina; O. Yewande Oshodi; Adebayo R. Erinfolami; Joseph D. Adeyemi; Tajudeen. F Suleiman (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2015)
Background: Studies on attitudes towards mental health in Nigeria have been mainly community-based surveys. Objective: To determine the knowledge and attitudes towards mental illness (MI) of health workers in a Nigerian Teaching Hospital. Methods: A stratified sample of 256 health workers completed an Attitude to Mental Illness Questionnaire (AMIQ) designed for this study. Results: Most participants (62.1% to 80.9%) identified scientific factors such as genetic inheritance as causes of MI; 24.8% identified spiritual factors as potential causes. Effective methods of treatment identified by respondents include orthodox methods (84.6%) and a combination of traditional and orthodox management (37.8%). There were varying shades of negative attitudes towards mentally ill persons (MIPs). Conclusion: The health workers showed some degree of social distance to MIPs, and there is need for psycho-education to improve their knowledge in mental health.